Team Approach: Preoperative Management of Metabolic Conditions in Total Joint Replacement. Issue 12 (December 2021) - Liu, Christina; Brinkmann, Elyse; Chou, Sharon H.; Tejada Arias, Karla; Cooper, Lisa; Javedan, Houman; Iorio, Richard; Chen, Antonia F.
Abstract : Total joint arthroplasties (TJAs) of the knee and hip have been considered 2 of the most successful surgical procedures performed to date. Frailty is defined as increased vulnerability to adverse outcomes with physiologic stress. Preoperative optimization of frailty and metabolic bone conditions, including osteoporosis, vitamin D deficiency, and diabetes, through a multidisciplinary approach can help improve outcomes and minimize costs after TJA.